Phosphate mediated changes in fatty acid composition in Neurospora crassa. - S. Ram; B. G. Nair; H. S. Chhatpar (Fungal Genetics Reports, 1984)
Phosphate mediated changes in fatty acid composition in Neurospora crassa.